(untitled) (Journal of Bio-Science, 2024)
The global population is steadily increasing, including in Bangladesh, and this necessitates the exploration of new technologies to meet the future demand for fish and biofloc technology holds great potential. Unfortunately, there is a dearth of information regarding biofloc culture technology in Bangladesh. Therefore, the purpose of this study was to identify a suitable probiotic for achieving rapid floc maturation. The research was taking place at the Pran Fisheries Project located in Razapur village, under the Sreemangal Upazilla in the Moulvibazar district, from 01 October to 15 October 2021. Thus, four different probiotics, namely Everfresh-Pro, PondCare-3S, Profs, and MI Plus, were tested and each one exhibited distinct mean value. Throughout the floc maturation process, consistent conditions were maintained, including a temperature range of 27-30°C, dissolved oxygen (DO) levels of 6 ppm, pH of 7.8, total dissolved solids (TDS) concentration of 980 ppm, and salinity of 0.8 ppt for all probiotics. The results revealed flocculation measurements of 28 mL for Everfresh-Pro, 23 mL for PondCare-3S, 20 mL for Profs, and 15 mL for MI Plus, as determined by the Imhoff Cone. The utilization of Everfresh-Pro probiotic results in a shorter FCO (Fermented Carbon Organic) production time among the other probiotics within biofloc system. These findings emphasize the significant potential of employing suitable probiotics in FCO making process, as it can substantially reduce maturation time and enhance the quality of floc, ultimately leading to more efficient and effective aquaculture practice through biofloc technology. J. Bio-Sci. 31(2): 1-12, 2023